Sistem Informasi Presensi Guru Berbasis QR-Code Pada SMAN 1 Waylima - Fitriani, Salwa Nur; Puspitasari, Tuti; Mukodimah, Siti (Institut Bakti Nusantara, 2025)
Efficient and accurate teacher attendance management is a crucial aspect of educational administration. Therefore, a system capable of recording attendance quickly and minimizing data errors is essential. This study aims to develop a QR Code-based teacher attendance information system using the Waterfall method and PHP programming language. The Waterfall method was chosen due to its systematic, sequential approach in software development, which includes requirements analysis, system design, implementation, testing, and maintenance. Data collection methods used in this research include observation, interviews, and literature review. The system utilizes QR Code technology for attendance processes, where each teacher has a unique code scanned upon arrival. The results show that the system improves the efficiency and accuracy of attendance recording compared to conventional methods. Additionally, it simplifies attendance data management and provides real-time access to reports for relevant stakeholders